Aplicação de um modelo cognitivo para análise de tomada de decisão em ambiente de desenvolvimento orçamentário - Marin, Rodrigo de Souza (2010)
The models usually used by the companies to monitor and to foresee the decision making process, searching for the ideal level of success in decisions, in many cases they are not appropriate. This happens because many of these decisions involve aspects that could not be foreseen in the rational models of the decision making process, like the intuition of the decision maker, that is shown by the use of heuristics or inclinations of decision, because of the preference of the decision maker in using certain alternatives instead of others, because of affectionate aspects (emotional and motivational). In the areas of Economy and Marketing there are several interdisciplinary studies relating themes of those areas, such as Neuroscience and Cognitive Psychology, seeking to better understand those aspects denominated Intuition and that are considered "the black box" of the economical models of decision. In Accounting that approach is still incipient. Thus, this study tries to understand the decision making process in accounting atmospheres, having a model of decision anchored in the Cognitive Psychology as a base. Therefore, its goals are: identifying the form of processing the information in the decision making process, when it involves the establishment of levels of budgetary goals, considering aspects that stray from rationality. The research was developed with quantitative focus, in the company Natura Cosméticos S.A., using a theoretical model proposed by researchers that study the theme of Neuroaccounting. Modelling of structural equations was used with the methodology PLS (Partial Least Squares). The results show that in Natura the theoretical model used as a base is strong, there are convergence points with the model of decision estimated by other researchers in other companies, but there are three aspects that are different in the decision making process of Natura with a model used for comparison: 1) information has significant weight to decision making, although it is to sustain decisions taken based in expertise; 2) there is social influence in the decision making process, in the moment of selecting incentives for decision, or in the analysis of the consequences of the decision; 3) the fear of making decisions is smaller, suggesting larger daring when estimating the budgetary goals. The results are coherent with the atmosphere of innovation of Natura and with its culture that focuses relationships. Future studies in the area of Behavioral Accounting will analyze if those characteristics can be widespread to other innovation atmospheres.